2022
DOI: 10.3324/haematol.2022.281110
|View full text |Cite
|
Sign up to set email alerts
|

Molecular monitoring of T-cell kinetics and migration in severe neurotoxicity after real-world CD19-specific chimeric antigen receptor T cell therapy

Abstract: CD19-specific chimeric antigen receptor (CD19-CAR)-T cell therapies mediate durable responses in late-stage B-cell malignancies, but can be complicated by a potentially severe immune effector cell-associated neurotoxicity syndrome (ICANS). Despite broad efforts, the precise mechanisms of ICANS are not entirely known, and resistance to current ICANSdirected therapies (especially corticosteroids) has been observed. Recent data suggest that inflammatory cytokines and/or targeting of cerebral CD19-expressing peric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Moreover, recently proposed predictive scores for CRS and ICANS, integrating laboratory and clinical data, might be used to find optimal prophylactic and/or early corticosteroid regimens in order to prevent high-grade CRS and ICANS [25,41,42]. Finally, recent data on the underlying mechanisms of CAR T-mediated neurotoxicity have suggested that CAR Tcells may allow other cytotoxic T-cells across the blood-brain barrier and that corticosteroids only insufficiently antagonize this T-cell infiltration [43]. Further translational research is needed to provide mechanistic insights and uncover novel therapeutic strategies for more effective prevention and management of ICANS.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recently proposed predictive scores for CRS and ICANS, integrating laboratory and clinical data, might be used to find optimal prophylactic and/or early corticosteroid regimens in order to prevent high-grade CRS and ICANS [25,41,42]. Finally, recent data on the underlying mechanisms of CAR T-mediated neurotoxicity have suggested that CAR Tcells may allow other cytotoxic T-cells across the blood-brain barrier and that corticosteroids only insufficiently antagonize this T-cell infiltration [43]. Further translational research is needed to provide mechanistic insights and uncover novel therapeutic strategies for more effective prevention and management of ICANS.…”
Section: Discussionmentioning
confidence: 99%
“…ICANS is another common complication of CAR-T therapy [ 120 , 121 ]. However, the pathogenesis of ICANS is still unclear [ 122 ]. The possible cause is the increase in inflammatory cytokines and activation of endothelial cells, increasing vascular permeability and disrupting BBB, resulting in many cytokines and chemokines entering the CNS, thus causing injury [ 123 ].…”
Section: Car-t Cell Therapy In Gbmmentioning
confidence: 99%